If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 19 + -3k Solving 6 = 19 + -3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3k' to each side of the equation. 6 + 3k = 19 + -3k + 3k Combine like terms: -3k + 3k = 0 6 + 3k = 19 + 0 6 + 3k = 19 Add '-6' to each side of the equation. 6 + -6 + 3k = 19 + -6 Combine like terms: 6 + -6 = 0 0 + 3k = 19 + -6 3k = 19 + -6 Combine like terms: 19 + -6 = 13 3k = 13 Divide each side by '3'. k = 4.333333333 Simplifying k = 4.333333333
| X-2(1+3x)=7x-4(2-3x)-18 | | -70m^5/-42mn^7 | | -(x-5)=2 | | (-x-5)=2 | | 8x-41=15 | | P-7/12=-1 | | 2(4+10)=8X+K | | -3(n-9)=63 | | 31u^8-(-4u^8)= | | -8(v+3)+2v+5=8v+11 | | 4x-(9x+9)=7x-21 | | 3m-2m=12 | | 7z-4=7 | | 4w+32-2w=2 | | 10w-6w=16 | | 14x-5=9-6x | | 3x+12=104 | | 3v-2=-23 | | 11x-6(2+3x)=5(x-2)-12x | | V-7/22=-1 | | X(3+5)= | | f(x)=1/2logx-4 | | X+3y+200-2x-2y=250 | | 3(4x-7)+8=6(2x+5)-7 | | 9n-8n=18 | | -2u+3=3u+6 | | 2(4+X)=38+2X | | 5x-13=89 | | 6a-3=3a-9 | | 5k-4k=13 | | 4(2x-4)-16(3x-1)=0 | | (x^3)^1/3=16^1/3 |